GROUP APPROACHES IN GUIDANCE AND COUNSELING SERVICES - Habsy, Bachrudin All; Ichwan, Rahma Kamila Nurul; Ardhana, Amelia Nidialuna; Wangi, Ayu Sekar; Habibah, Mayda Nurul (PT Altin Riset Publishing, 2024)
This study was made to describe and analyze the various types of counseling guidance services with a group approach used in guidance and counseling practice. Group approach in guidance and counseling is one of the approaches used by professionals in providing guidance and counseling services to a group of individuals who have similar problems or needs. Through a literature review of relevant sources, this research involves systematic problem identification and analysis of scholarly publications related to the types of guidance and counseling services with a group approach. The results of this research include the definition of group guidance, the definition of group counseling, the types of group guidance and counseling services, and the stages of group guidance and counseling. By providing a detailed view of the types of group guidance and counseling services, this research aims to provide helpful insights for guidance and counseling professionals in designing and providing services that suit the needs of their clients.